USE OF INNOVATIVE PEDAGOGICAL TECHNOLOGIES IN PHYSICAL EDUCATION OF PRESCHOOL CHILDREN (ResearchJet Journal of Analysis and Inventions, 2021)
The use of innovative pedagogical technologies in the physical education of children in preschool education and its advantages.